Healthcare performance for patients with heart failure in Iran: addressing the tip of the iceberg - Fateme Gorgani; Mohammadreza Naderian; Shahab Khatibzadeh; Ahmad Amin; Yosef Farzi; Mohammad Reza Beyranvand; Majid Haghjoo; Mitra Modirian; Nazila Shahbal; Mehrdad Azmin; Saeid Shahraz (BMC Health Services Research)
Abstract Background Chronic diseases, such as heart failure with reduced ejection fraction (HFrEF), remain significant factors in the healthcare burden in Iran. Healthcare systems must have comprehensive data on the current usage, costs, and quality of care to tackle these challenges and formulate strategic plans effectively. Methods The study included 209 patients with a mean age of 58 years (SD = 16.5) who met the inclusion criteria of having an ejection fraction of less than 40% and a confirmed diagnosis of HFrEF. This study used nationally representative data to assess the healthcare usage, costs, and quality of HFrEF management in Iran. Results The most used services were medication dispensing (76%) and outpatient visits (53%), while rehabilitation (3%) and homecare (2%) were used less frequently. The annual per-patient direct medical cost was $1,464, with $308 (21%) paid out-of-pocket (OOP). Hospitalization accounted for most of the total cost (68%), and pharmacy expenses comprised the largest portion of OOP payments (46%). Echocardiography was performed for 91.1% of patients upon admission. Only 71.6% of patients had arrangements for a cardiology visit within seven days following hospital discharge. Additionally, only 67.5% of patients received prescriptions for angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, and 85% were prescribed beta-blockers. Conclusion Patients with heart failure in Iran face challenges in accessing adequate cardiac care, including a lack of care continuity and advanced cardiac services. The study provided an essential benchmark for future healthcare reform.